Incidence of Lower Limb Lymphedema in Post therapeutic Gynaecological Malignancies (International Journal of Physiotherapy, 2023)
Introduction: Lower limb lymphedema (LLL) is one of the most disabling side effects of surgical and radiotherapy treatment for gynecological cancers (carcinoma of the cervix, carcinoma of the ovary, carcinoma of the endometrium, and carcinoma of the vulva). The incidence of lymphedema varies in gynecological cancers and patients undergoing radiotherapy and surgery. This prospective study aims to determine the incidence of lower limb lymphedema after surgery and radiotherapy in gynecological malignancies.Methodology: A total of 512 subjects who undergo treatment for gynecological malignancies in the department of surgical oncology and / or radiotherapy were screened to find out the incidence of lymphedema by measuring limb circumference with inch tape and extracellular fluid (ECF) volume with bio-impedance analyzer at four intervals, before surgery/ radiotherapy, after surgery/radiotherapy, three months follow-up and six months follow-up. The limb circumference and ECF were used to find out the lymphedema.Results: Turkey's pairwise comparison test was carried out to determine the incidence of lymphedema in both subjects (radiotherapy & surgery). The percentage of incidence of lymphedema in subjects who have undergone radiotherapy and surgical treatment with gynecological malignancies is 18.94% overall.Conclusion: Many subjects developed lymphedema with post-treatment gynecological malignancies. It causes significant functional problems, emotional disturbances, adversely affecting the quality of life, and it also causes a financial burden to the family. Lymphedema can be diagnosed initially using a Bio-impedance analyzer and inch tape to minimize the complications and progression of the disease.